Enhancing resistant starch fraction in modified elephant foot yam starch: optimizing preparation conditions and exploring tribological properties - Barua, Sreejani; Srivastav, Prem Prakash; Vilgis, Thomas A. (Frontiers in Food Science and Technology, 2024)
Introduction Elephant foot yam starch is highly susceptible to enzymatic digestion. To address this, heat-moisture treatment (HMT) has been used to modify its digestive properties and functionalities. However, when using modified starch in various food compositions, it is ultimately necessary to cook it in water-rich environments. The present work thus offers a systematic understanding of the heating and cooking procedures for modified starch, with a view to maintaining its structural and digestive properties. Methods Experimental investigations employing X-ray diffraction, scanning electron microscopy, and enzymatic digestion have been utilized to gain insights into the characteristics of cooked starches. The interactions between amylose and amylopectin in native starch are more susceptible to disruption during cooking, which results in changes in texture and a reduction in resistant starch (RS) retention. Additionally, these preparations have been investigated by tribology to test structure and and friction. Results and discussion The application of HMT has been observed to induce changes that stabilize the interactions between amylose and amylopectin, thereby ensuring better maintenance of granular integrity and higher RS retention under specific cooking conditions. The findings indicate that following a 2-min cooking period at 100°C, the modified elephant foot yam starch (EFYS) demonstrated enhanced granular stability, which was subsequently compromised after 10 min of cooking. Additionally, when modified elephant foot yam starch (EFYS) was heated at a temperature of 86°C for 2 and 6 min, it demonstrated superior preservation of resistant starch (RS) in comparison to a cooking time of 10 min. Moreover, the HMT starch exhibited the highest RS retention when cooked at 100°C for 2 and 6 min at approximately 39.12% and 20.23%, respectively. However, this retention decreased significantly to 1.08% after 10 min of cooking. Furthermore, the insights from tribology, when combined with the proposed naive models, enhance the understanding of how preparation conditions affect the functionalities of starches, which is crucial for designing food products with desired textural and nutritional qualities, especially in water-rich environments, where maintaining structural integrity and RS content is important.